2022
DOI: 10.1158/2767-9764.crc-22-0258
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor DNA Monitoring Reveals Molecular Progression before Radiologic Progression in a Real-life Cohort of Patients with Advanced Non–small Cell Lung Cancer

Abstract: Purpose The clinical potential of liquid biopsy in advanced cancer patients is real-time monitoring for early detection of treatment failure. Our study aimed to investigate the clinical validity of circulating tumor DNA (ctDNA) treatment monitoring in a real-life cohort of advanced Non-Small Cell Lung Cancer (NSCLC) patients. Patients and Methods Advanced or non-curative locally advanced NSCLC patients were prospectively included in an exploratory study (NCT03512847). Selected cancer-specific mutations were me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…In patients with metastatic CRC treated with an anti-EGFR monoclonal antibody, treatment-emergent, subclonal alterations in KRAS, MET, and EGFR extracellular domain (ECD) causing acquired resistance to anti-EGFR were detectable in plasma as early as 10 months prior to the clinical tumor progression [22,44,45]. In CRC, breast cancer, and NSCLC treated with chemotherapy, longitudinal monitoring of ctDNA was able to detect molecular progression with a median molecular lead time of 1.3-3.3 months [36,46,47]. Whether "molecular progression" revealed by ctDNA monitoring has a true clinical significance, however, can only be determined by demonstrating that early treatment modification based on ctDNA results (e.g., early introduction of a subsequent line of treatment or therapy targeting somatic alterations identified by ctDNA) improves long-term survival or quality of life.…”
Section: Tumor Dynamics Monitoring During Treatmentmentioning
confidence: 99%
“…In patients with metastatic CRC treated with an anti-EGFR monoclonal antibody, treatment-emergent, subclonal alterations in KRAS, MET, and EGFR extracellular domain (ECD) causing acquired resistance to anti-EGFR were detectable in plasma as early as 10 months prior to the clinical tumor progression [22,44,45]. In CRC, breast cancer, and NSCLC treated with chemotherapy, longitudinal monitoring of ctDNA was able to detect molecular progression with a median molecular lead time of 1.3-3.3 months [36,46,47]. Whether "molecular progression" revealed by ctDNA monitoring has a true clinical significance, however, can only be determined by demonstrating that early treatment modification based on ctDNA results (e.g., early introduction of a subsequent line of treatment or therapy targeting somatic alterations identified by ctDNA) improves long-term survival or quality of life.…”
Section: Tumor Dynamics Monitoring During Treatmentmentioning
confidence: 99%
“…The analysis of ctDNA allows for monitoring the response to treatment in realtime regimens, including the detection of molecular residual disease, which has been described for lung cancer [101,[111][112][113], colorectal cancer [114], ovarian cancer [115], and others [87,116,117]. It was found that the use of the methylation markers for a number of genes allows not only for the identification of patients with colorectal cancer, but also for monitoring recurrence [95].…”
Section: Possible Applications Of Ctdna In Oncologymentioning
confidence: 99%